Ultrasound-assisted extraction of phytohormones from vermicompost. - Teo, Chee How. (2012)
Vermicompost (VC) is the by-product of the joint actions between earthworms and microorganisms living within them and is traditionally used as organic fertilizer. It is postulated that phytohormones are the “magic compounds” in VC that made them such good fertilizers. Chemical characterization of phytohormones in VC is seldom reported. Our aim is to develop an efficient extraction method for the simultaneous extraction of different classes of phytohormones in VC using ultrasound-assisted extraction (UAE). The efficiency of this technique was compared with the classical mix-stirring (MSt) method. Nine phytohormones from three different classes: trans-zeatin (Z), kinetin (K), indole-3-acetic acid (IAA), N6-[2-Isopentyl]adenine (iP), N6-Benzyladenine (BA), N6-Isopentenyladenosine (iPR), (+)-Abscisic Acid (ABA), 4-[3-Indolyl]butyric Acid (IBA) and 1-Naphthaleneacetic Acid (NAA) were screened in this project. Systematic optimization was conducted based on the various parameters. Compared to MSt, UAE proved to be more time efficient and was able to achieve higher recovery with lesser solvent usage. The optimized conditions for UAE were using either MeOH- or EtOH-water-acetic acid, 80:20:1, v/v/v, with no significant difference between them, 40min extraction time and solvent to sample ratio of 16:1. These extraction parameters were applied on a qualitative study of 500g real VC sample and iP was detected under LC-MS.